Republic of Poland : Selected Issues Paper. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper considers the case of Poland to analyze global financial spillovers to emerging market (EM) sovereign bond markets. Foreign holdings of Polish government bonds have increased substantially over the last decade. Although foreign participation in local-currency sovereign bond markets provides an additional source of financing and reduces sovereign yields, it has also given rise to concerns about increased sensitivity to shifts in market sentiment. The analysis in this paper suggests that foreign participation plays an important role in transmitting global financial shocks to local-currency sovereign bond markets by increasing yield volatility and, beyond a certain threshold, amplifying these spillovers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet